Uji Aktivitas Sitotoksik Ekstrak Dan Fraksi Dari Spon Laut Petrosia sp. Dengan Metode Brine Shrimp Lethality Test - Dian Handayani; Lendra Yunance; Krisyanella Krisyanella (STIFARM Padang, 2011)
The determination of cytotoxic of the marine sponge Petrosia sp. using Brine Shrimp Lethality Test has been done. The cytotoxic activity analysis were done toward condensed extract, n-hexane, ethyl acetate and butanol fractions and yielded LC50 value 70.736 ppm, 269.153 ppm, 197.38 ppm and 70.667 ppm respectively. It shown that butanol fraction was more cytotoxic than the other fractions.